Analisis Praktik Klinik Keperawatan Penerapan Intervensiterapi Finger Hold Terhadap Tingkat Nyeri Pada pasien Cedera Kepala Ringan - Novita Efendi; Fadli Syamsuddin (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Introduction: Head injury is a traumatic disorder of brain function that does not result in a disconnection of brain continuity and can occur with or without interstitial hemorrhage of the brain substance. Purpose:Acute pain is one of the nursing problems experienced by patients with head injuries. To analyze the application of finger hold therapy interventions in reducing pain in patients with mild head injuries. Research methods: is Pre Experimental, which is a design with a One group pre test post test design approach, when this study was carried out from December 21, 2022 to January 23, 2023, with a sample of 6 patients. Research Results: The frequency of patients who experienced moderate pain levels before treatment was 4 patients (66.7.7%), and severe pain levels were 2 patients (33.3%) while the distribution of psien frequency who experienced mild pain levels after treatment was 3 respondents (50.0%), moderate pain levels were 1 patient (16.7%) and berst pain levels were 2 patients (33.3%). This shows that there is no change in pain levels in patients with severe pain scales, because finger hold terap cannot be applied to patients with severe pain levels.Conclusion :This study showed that there is an effect of finger hold therapy in reducing pain in patients with mild head injuries